Effect of Apple Dregs Mass and Processing Time on Pectin Extraction from Apple Dregs - Roberto Mario Belo; Kun Aussieanita Mediaswanti (Universitas Tribhuwana Tunggadewi Malang, 2022)
Apples have the opportunity to develop their potential to the fullest. In the process of taking apple cider, apple dregs will be obtained. The dregs can be further processed or extracted to obtain pectin. This research was conducted to determine the optimum extraction time and mass to produce pectin from apple dregs. The experimental procedure includes raw material preparation, extraction, distillation, drying, and yield analysis. The method used is solid-liquid extraction using ethanol solvent. Time and mass of apple dregs and temperature according to the changing variables that have been determined, namely for the variable extraction time 120 minutes, 150 minutes, and 180 minutes, while the mass of dry apple dregs was 65 grams, 70 grams, and 75 grams while the operating temperature remained 70°C and the precipitating agent used is alcohol or 95% ethanol with 50% acetic acid as a solvent, as well as analysis of pectin content by spectrophotometry (UV-VIS). The study results showed the lowest concentration of 0.002 ppm and the lowest absorbance of 0.006 nm. Where the highest concentration is 2.5 ppm, and the highest absorbance is 0.241 nm, a calibration curve is formed linearly where y = 0.0936x + 0.0111 and R2 = 0.9931. From the results of the graphical analysis of the relationship between the effect of concentration and mass on time in the apple dregs pectin extraction process, the highest concentration was 1.9 ppm at mass 70 with a time of 180 minutes, and the lowest concentration was 0.7 ppm at mass 65 with a time of 120 minutes.